Application of Novel Fulvic Acid-Coated Magnetite Nanoparticles for CO2−-Mediated Photoreduction of Cr(VI) - Arce, Valeria Beatriz (2018)
We here isolate fulvic acids from vermicompost to prepare and characterize novel fulvic acid-coated magnetite nanoparticles. UV-A irradiation of suspensions of the nanoparticles under different experimental conditions led to photoreduction of Cr(VI). In anoxic conditions in the presence of formic acid, after 60 min of irradiation ca. 100% of Cr(VI) was reduced. Under these conditions, the carbon dioxide radical anions, CO2 .-, mediated the photo-reduction of Cr(VI). However, the high reduction potential of Cr(VI) and the variety of reactive species generated upon UV-A irradiation make this nanomaterial also suitable for Cr(VI) photo-reduction also under aerobic conditions in the presence of formic acid or under anoxic conditions without the addition of formic acid. The possible photodegradation routes involved are discussed in detail.